Interpreting Entrepreneurial Transitions Through the Narratives of Entrepreneurial Support Organizations (ESO): A Study in Solo, Central Java - Edy Tri Atmojo; Kartika Wulandari; Bagus Yudistira; Sry Setyaningrum (CV. Vocezmi Learnov, 2026)
This study aims to examine how Entrepreneurial Support Organizations (ESOs) construct and disseminate narratives that shape entrepreneurial transitions among Micro, Small, and Medium Enterprises (MSMEs) in Solo, Central Java, particularly in the context of digital transformation and ecosystem development. The research employs a qualitative multiple-case study approach, drawing on in-depth interviews, participant observation, and document analysis involving MSME actors and two key ESOs. Data were analyzed using thematic and narrative analysis to capture patterns of identity construction, ecosystem orientation, and future-oriented sensemaking. This study contributes to the transitional entrepreneurship literature by foregrounding narratives as a central mechanism through which ESOs shape entrepreneurial identities, ecosystem positioning, and collective futures, extending ecosystem-based perspectives beyond instrumental support functions. Findings highlight the strategic role of ESOs in fostering digital literacy, collaboration, and inclusive ecosystem development, offering insights for policymakers and practitioners to design more narrative-sensitive and equity-oriented support programs. The study is limited to two ESOs within a single local context, suggesting opportunities for future research across diverse regions and broader ecosystem actors using comparative or discourse-based approaches.